The Association of Olfactory Dysfunction, Frailty, and Mortality Is Mediated by Inflammation: Results from the InCHIANTI Study - Alice Laudisio; Luca Navarini; Domenico Paolo Emanuele Margiotta; Davide Onofrio Fontana; Irene Chiarella; Daniele Spitaleri; Stefania Bandinelli; Antonella Gemma; Luigi Ferrucci; Raffaele Antonelli Incalzi (Journal of Immunology Research)
Background. Olfactory dysfunction might unveil the association between ageing and frailty, as it is associated with declining cognitive function, depression, reduced physical performance, reduced dietary intake, and mortality; all these conditions are characterized by increased levels of inflammatory parameters. The present study is aimed at evaluating the association between olfactory dysfunction, frailty, and mortality and whether such association might be mediated by inflammation. Methods. We analysed data of 1035 participants aged 65+ enrolled in the “InCHIANTI” study. Olfactory function was tested by the recognition of the smells of coffee, mint, and air. Olfactory dysfunction was defined as lack of recognition of at least two smells. Considering the items “shrinking,” “exhaustion,” “sedentariness,” “slowness,” and “weakness” included in the Fried definition, frailty was defined as the presence of at least three criteria, prefrailty of one or two, and robustness of none. Serum interleukin-6 (IL-6) was measured in duplicate by high-sensitivity enzyme-linked immunosorbent assays. Logistic regression was adopted to assess the association of frailty with olfactory function, as well as with the increasing number of olfactory deficits. Cox regression was used to test the association between olfactory dysfunction and 9-year survival. Results. Olfactory dysfunction was associated with frailty, after adjusting (OR 1.94, 95% CI=1.07-3.51; P=.028); analysis of the interaction term indicated that the association varied according to interleukin-6 levels (P for interaction=.005). Increasing levels of olfactory dysfunction were associated with increasing probability of being frail. Also, olfactory dysfunction was associated with reduced survival (HR 1.52, 95% CI=1.16-1.98; P=.002); this association varied according to the presence of frailty (P for interaction=.017) and prefrailty status (P for interaction=.046), as well as increased interleukin-6 levels (P for interaction = .011). Conclusions. Impairment of olfactory function might represent a marker of frailty, prefrailty, and consequently reduced survival in an advanced age. Inflammation might represent the possible link between these conditions.